Molecular Mechanisms of Neurotransmitter Release - Wang, Zhao-Wen (Advances in Neurobiology, 2008)
Within the complex neuronal network of the nervous system, neuron-to-neuron communication occurs mainly through chemical synapses, where the presynaptic nerve terminal releases neurotransmitters that control the function of postsynaptic neurons by acting on postsynaptic receptors. Recent decades have brought groundbreaking new developments and a wealth of knowledge to this field. In Molecular Mechanisms of Neurotransmitter Release, leading experts provide concise, up-to-date information on all major molecular mechanisms involved, with complete background information and figures and diagrams to further elucidate key concepts or experiments. Comprehensive and cutting-edge, Molecular Mechanisms of Neurotransmitter Release is sure to provide a learning tool for neuroscience students, a solid reference for neuroscientists, and a source of knowledge for all those who have a general interest in the ever-evolving field of neuroscience.